P. A. Oyunsky’s Poem “Byrastɨ”: A Philological Analysis - Popova, Matryona Petrovna; Dishkant, Elena Valeryevna; Chirkoyeva, Daria Ivanovna (Journal of History Culture and Art Research, 2018)
This article attempts to conduct a literary analysis of the poem titled Byrastɨ (Farewell), which is a work of a classic Yakut writer P.A. Oyunsky. One of the best works written by the classic Yakut writer, Platon Oyunsky "Byrastɨ" was previously regarded by scholars from the point of view of the literary analysis approach. In order to give a more objective insight of the concept and content behind this poetic masterpiece, the authors of the article completed a full philological analysis, which includes both - literary and linguistic research; the authors of the article singled out linguistic units, semantic fields and analyzed the grammatical structure of the text. Fundamental works of Y. Lotman, R. Jakobson, D. Magomedova, M. Gasparov served as the theoretic and methodological basis for the article. The research findings presented by above mentioned scholars justify the necessity to complete a structural analysis of the non-fiction work on the phonological, stylistic levels as well as the conceptual and imagery level. Based on the systematic philological analysis of the poem under study, we have come to the following conclusions: being and innovative poet, P. Oyunsky mastered his skills reaching a high level of professionalism; this can be vividly seen on the phonological level of the poem: it contains equally represented cases of vertical and horizontal alliteration as well as phonomorphological (grammatically homogenous) rhyme. Using the image of the sea as a symbol, the main character says farewell to his life sensing that the end is near. The poem became a requiem for the poet; because of this, it contains a prevailing number of nouns with predominantly 1st person possessive affixes. This allows the poet to express his deepest thoughts. The verb forms are represented by figurative and onomatopoetic words, which give the poem not only its lyricism but also solemnity. This poem became a profound work of the poet. It contains all the themes that he expressed in his creative work; the following thematic fields can serve as an example: "human and nature", "time and space", "human and society", "death", "the poet and immortality". The author’s turning to the image of the sea, shows that Oyunsky followed the aesthetic principles of Romanticism and the traditions of Russian literature established by A. Pushkin, M. Lermontov, and M. Gorky.